DAMPAK PERUBAHAN BUDAYA DI KOTA BAUBAU TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; St Nurhadijah; Windi Risma Yanti (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This research examines the impact of cultural shifts in Baubau City on the learning patterns of elementary school students. As the former center of the Buton Sultanate, Baubau possesses a rich cultural heritage, yet globalization has introduced digital behaviors that challenge traditional educational values. The study identifies a decline in the application of local philosophies, such as "Pobinci-binci Kuli" and "Poma-maasiaka," in the classroom setting. Using a qualitative descriptive approach, data were gathered through interviews with educators and observations in several public elementary schools in Baubau. The findings reveal that digital culture has created a gap in students' social interactions and diminished their interest in local wisdom-based content. The study concludes that there is an urgent need for the integration of Butonese local wisdom into the modern curriculum to preserve cultural identity. This integration serves as a logical consequence for developing Islamic educational praxis in the region. Keywords: Baubau City, Buton Culture, Cultural Change, Elementary School, Local Wisdom.This research examines the impact of cultural shifts in Baubau City on the learning patterns of elementary school students. As the former center of the Buton Sultanate, Baubau possesses a rich cultural heritage, yet globalization has introduced digital behaviors that challenge traditional educational values. The study identifies a decline in the application of local philosophies, such as "Pobinci-binci Kuli" and "Poma-maasiaka," in the classroom setting. Using a qualitative descriptive approach, data were gathered through interviews with educators and observations in several public elementary schools in Baubau. The findings reveal that digital culture has created a gap in students' social interactions and diminished their interest in local wisdom-based content. The study concludes that there is an urgent need for the integration of Butonese local wisdom into the modern curriculum to preserve cultural identity. This integration serves as a logical consequence for developing Islamic educational praxis in the region.